The Illusion of Spirituality in Legal Professions: Administrative Reductionism and Notary Appointment Integrity in Indonesia - Henry Halim; Imeldalius; Yudadibrata; Novrida Fauziyah Nasution (Arkus, 2024)
The Indonesian Law on Notarial Positions places devotion to God Almighty—the principle of spirituality—as the foremost prerequisite for notary appointment, yet rising notarial malpractice signals a disconnect between this transcendental mandate and substantive professional integrity. This convergent mixed-methods socio-legal study examined how regulatory authorities interpret and verify the spirituality requirement, and how stakeholder perceptions of that verification predict support for reform, within a province on the western seaboard of Indonesia governed by Islamic-Malay customary law. The qualitative strand comprised fifteen in-depth interviews and document analysis across three anonymized clusters; the quantitative strand surveyed 185 legal-profession stakeholders using five validated five-point scales (Cronbach’s α 0.81–0.89). Respondents rated administrative reductionism high (mean 4.06, 95% CI 3.97–4.15) and perceived verification adequacy low (mean 2.39, 95% CI 2.28–2.50). Multiple regression explained 60.5% of variance in support for the proposed Spiritual-Integrous Recruitment model (R²=0.605; F(4,180)=68.84, p<0.001; Cohen’s f²=1.53), with administrative reductionism (β=0.312), living-law integration deficit (β=0.242), institutional inertia (β=0.216) and perceived adequacy (β=−0.293) as significant predictors (all p<0.001). Perceived adequacy differed across clusters (ANOVA F(2,182)=6.90, p=0.001, η²=0.07), lowest in the resource-rich semi-urban cluster. Qualitative themes—administrative reductionism, institutional inertia, and disconnect from living law—triangulated the survey. The state secularizes an ethical mandate into a documentary checklist, marginalizing integrity. The study proposes the Spiritual-Integrous Recruitment model, integrating psychometric integrity testing with living-law screening, to convert a dogmatic illusion into a measurable safeguard of legal professionalism.